2012
DOI: 10.1123/japa.20.3.281
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Theory of Planned Behavior Intervention for Older Adults With Type 2 Diabetes and Cardiovascular Disease

Abstract: A randomized controlled trial evaluated the effectiveness of a 4-wk extended theory of planned behavior (TPB) intervention to promote regular physical activity and healthy eating among older adults diagnosed with Type 2 diabetes or cardiovascular disease (N= 183). Participants completed TPB measures of attitude, subjective norm, perceived behavioral control, and intention, as well as planning and behavior, at preintervention and 1 wk and 6 wk postintervention for each behavior. No significant time-by-condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 54 publications
8
41
5
Order By: Relevance
“…cation, which was in the line with the current study findings (35). However, White et al, reported no statistically significant changes after the intervention in the attitudes toward healthy diet (35).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…cation, which was in the line with the current study findings (35). However, White et al, reported no statistically significant changes after the intervention in the attitudes toward healthy diet (35).…”
supporting
confidence: 81%
“…The study by Senior Angulo et al, (40) stated that the mean score of intention increased significantly after the TPB-based intervention. However, White et al, reported that the intention to engage in healthy diet was not significantly different between the intervention and control groups, postintervention (35). It should be noted that although interventions targeting behavioral, normative, or control beliefs may succeed in producing the changes attributed to attitudes, subjective norms, and PBC, and finally individuals' intention toward desired direction, the intervention would have no effect unless the individuals are able to carry out these intentions.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Intention reflects one's motivation and willingness for behavior involving (Ajzen, 1991;Hagger & Chatzisarantis, 2005) that is the main and direct determinant of a behavior (Rhodes et al, 2006;Vallance et al, 2011;Kosma, 2012). Furthermore, intentions are explained by three independent concepts, including attitude toward the behavior, subjective norm (perceived social pressure regarding to the particular behavior), and perceived behavioral control (perceived capability for conducting the behavior) (White et al, 2012). Together, these constructs are representative of a person's total motivation for performing the behavior (Kwan & Bryan, 2010).…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…White et al (2012) successfully increased physical activity within chronic disease sufferers by targeting identified motivational beliefs from the TPB alongside planning strategies. French et al (2012) found increases in walking behavior in a combined TPB motivation and volition intervention compared to those targeting motivation and volition separately.…”
Section: Motivation and Volitionmentioning
confidence: 99%